Detection of norovirus in food samples collected during suspected food‐handler‐involved foodborne outbreaks in Tokyo. (1st September 2019) - Somura, Y.; Nagano, M.; Kimoto, K.; Oda, M.; Mori, K.; Shinkai, T.; Sadamasu, K.
Abstract: Although norovirus (NoV) is the major cause of gastroenteritis, with the largest number of NoV food poisoning cases in Japan, limited information is available regarding NoV detection in food. This study aimed to detect NoV in food samples during the 2015–2016 suspected foodborne outbreaks in Tokyo; 352 food samples from 64 NoV food poisoning outbreaks were collected. Bacterial culturing was performed for sample pretreatment and real‐time reverse transcription polymerase chain reaction was conducted for NoV screening. The NoV detection rate was 1·7% (6/352). NoV‐positive food samples included leftover boxed lunch, mackerel fillet (foodstuff), aburi salmon slice (partially seared salmon slice), raw tuna as a chirashizushi ingredient, raw amberjack as a sushi topping and ice for drinks. Since fresh fish as sushi toppings or ingredients and ice were consumed without heating, they may present a higher risk of viral infection. NoV‐positive food samples were obtained from five outbreaks, wherein food handlers were NoV‐positive in four. Each partial VP1 sequence from food samples matched completely with those in NoV‐positive individuals and food handlers. Hence, food handlers play a potentially important role in food‐based NoV transmission in all five outbreaks; therefore, hygiene education among them is essential to prevent NoV foodborne outbreaks. Significance and Impact of the Study: Significance and Impact of the Study: Norovirus (NoV) is a leading cause of foodborne outbreak in Japan. The most frequent route of transmission in NoV foodborne outbreaks is secondary contamination via infected food handlers. However, limited information is available regarding NoV contamination in food samples. This study reports the detection of NoV in food samples to elucidate the source and route of NoV infection leading to outbreaks for 2 years in Tokyo. Our data potentially contribute to education and the development of safe food‐handling strategies among food handlers and employees in the food industry through elucidation of risk factors associated with NoV contamination.